2022
DOI: 10.1007/s11600-022-00910-8
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing and multi-criterion analysis for identifying suitable rainwater harvesting areas

Abstract: Water scarcity and soil erosion are the main constraints small holder farmers are facing in Tigray, the northern most part of Ethiopia. Both very high and very low precipitation can cause a damage to agriculture which is the case in semi-arid regions like Tigray. While too little rainfall cannot support the growth of crops resulting in crop failure, the short but intense rainfall also causes a runoff thereby washing away essential soil nutrients. Installation of different micro/macro-catchment rainwater harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Precipitation is a vital resource of the hydrological cycle [1,2]. Excessive rainfall can lead to a decrease in water quality, which is detrimental to both human health and ecosystem well-being [3,4]. Precipitation measurement is therefore essential for weather forecasting [5].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation is a vital resource of the hydrological cycle [1,2]. Excessive rainfall can lead to a decrease in water quality, which is detrimental to both human health and ecosystem well-being [3,4]. Precipitation measurement is therefore essential for weather forecasting [5].…”
Section: Introductionmentioning
confidence: 99%
“…the proposed woody species) are compared one to each other and a scoring system is used (Enescu, 2017;Patel & Blumberga, 2023;Wang et al, 2023). Due to its user-friendliness, adaptability, and cost-effectiveness (Debebe et al, 2023), AHP has found extensive application across various research domains over the past five decades. For instance, in Romania, AHP has been employed for selecting tree and shrub species for creating field shelterbelts (Enescu, 2018) or for salt-affected areas (Enescu, 2020).…”
Section: Figure 1 Location Of Dolj Countymentioning
confidence: 99%
“…Being simple to use, flexible and cost effective [61], AHP was widely used in several research fields in the last five decades. For example, in Romania, AHP was used to choose different tree and shrub species for the establishment of field shelterbelts [62] or to propose the most suitable solution for afforestation of sandy soils in Oltenia Plain and Carei Plain [47].…”
Section: Case Study: Implementation Of the Expert Modelmentioning
confidence: 99%